1978
DOI: 10.1136/bmj.2.6141.857
|View full text |Cite
|
Sign up to set email alerts
|

A method for self-assessment of disability before and after hip replacement operations.

Abstract: Summary and conclusionsA standardised form was developed to review the daily problems suffered by patients with arthritis of the hip and provide clinicians with information for planning treatment and in judging subsequent progress. The reports made by various patients in a preliminary study provided 81 statements on pain, restricted movements, and restricted activities that were then tested to identify the most reliable. The responses of 32 patients waiting for hip replacements and 66 patients who had undergon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 7 publications
(1 reference statement)
0
7
0
Order By: Relevance
“…All areas of health, with the exception of physical mobility in the long term, were significantly improved, with 60% or more of patients with a pre-operative problem reporting post-operative improvement. Such a reduction in NHP scores has also been observed in patients recovering from fractures (McKenna et al, 1984) and from hip replacement (McDowell et al, 1978).…”
Section: Socialmentioning
confidence: 60%
See 1 more Smart Citation
“…All areas of health, with the exception of physical mobility in the long term, were significantly improved, with 60% or more of patients with a pre-operative problem reporting post-operative improvement. Such a reduction in NHP scores has also been observed in patients recovering from fractures (McKenna et al, 1984) and from hip replacement (McDowell et al, 1978).…”
Section: Socialmentioning
confidence: 60%
“…The NHP has been successfully applied to a variety of patient groups including patients with osteoarthrosis (Hunt et al, 1981c), peripheral vascular disease (Hunt et al, 1982) fractures (McKenna et al, 1984), and those requiring minor surgery (Hunt et al, 1981a), hip replacement (McDowell et al, 1978) and cardiac transplantation (O'Brien et al, 1987). It has never, as far as we are aware, been applied to patients undergoing prostatectomy.…”
mentioning
confidence: 99%
“…Data from case series (references on request) and a comparative study36 confirmed that diverse functional scales are responsive to surgical intervention, but data on inter-rater reliability data were lacking except for one little used measure. 37 perform only few or none of the duties of usual occupation or of self care Class IV Largely or wholly incapacitated with patient bedridden or confined to wheelchair, permitting little or no self care and rheumatologists on the panel suggested considering two other factors. Firstly, reparative procedures such as osteotomy might mitigate need for arthroplasty in younger patients.…”
Section: Panel Process: Generation Of Case Scenariosmentioning
confidence: 99%
“…Examples include the RAND Medical Outcomes Study 36-Item Health Survey (also known as the SF-36) [40,41], the Quality of Well-Being Scale (QWB) [42][43][44], the Sickness Impact Profile (SIP) [45,46], and the Nottingham Health Profile (NHP) [47][48][49]. Each assesses various components of HRQOL, including physical and emotional functioning, social functioning, and symptoms.…”
Section: General Hrqol Instrumentsmentioning
confidence: 99%